A SURVEY FOR ZOONOTIC AND OTHER GASTROINTESTINAL PARASITES IN PIG IN BALI PROVINCE, INDONESIA - Widisuputri, Ni Komang Aprilina; Suwanti, Lucia Tri; Plumeriastuti, Hani (Indonesian Journal of Tropical and Infectious Disease, 2020)
Pigs have potentially to transmit zoonotic gastrointestinal parasite disease both caused by protozoa and worm. The aim of this study was to identify gastrointestinal parasites that were potentially zoonotic in pigs in the province of Bali. A total of 100 fresh feces samples was collected from several pig farms in Bali, from Badung and Tabanan districts, each consisted of 50 samples. Pig feces samples were examined for the presence of eggs worms, cysts and oocysts for protozoa based on the morphology and size. Identification for protozoa and worms used native, sedimentation and sucrose flotation methods. Parameters measured were sex, feed and cage management. The result showed that the characteristic parameters for pigs in both district were generally female. Cage management for raising pigs mostly used group cage. Feed that provided in both district mostly used bran and concentrate. All of 100 pig feces samples that examined positive for parasites. There were 8 types of gastrointestinal parasites that have been identified. Four types of protozoa found were Entamoeba sp. (99%), Balantidium sp. (79%), Eimeria sp. (78%), Blastocystis sp. (69%) and four types of worms were Ascaris sp. (20%), Trichuris sp. (20%), Strongyloides sp. (19%), and Oesophagostomum sp. (8%). All pigs were infected with two or more parasites. The prevalence of parasitic gastrointestinal infections was different for each district, six genera (Entamoeba sp., Balantidium sp., Blastocystis sp., Eimeria sp., Oesophagostomum sp. and Trichuris sp.)  were higher found in Tabanan district and the two genera (Ascaris sp. and Strongyloides sp.) were higher in Badung district. Oesophagostomum sp. was only found to infect pigs in Tabanan district. The conclusion is gastrointestinal parasites that found in pigs at Badung and Tabanan district Bali Province mostly have zoonotic potential.